Internal erosion of sandy gravels and occurrence of open-framework gravels in the subsoil of a river dike - Bonelli, Stéphane; Girolami, Laurence (Geomechanics for energy and the environment, 2025)
When a river dike is built on a sandy gravel paleo-valley, successive floods can induce internal erosion. This is the subject of this work, with a finite element analysis of a river dike system. This type of analysis makes it possible to find artesian and uplift zones in the protected floodplain, an element to be integrated into flood hazard mapping. The study area is the River Agly in southern France, where numerous leaks, sand boils and sinkholes have been observed along the dikes. The aim is to better understand the origin of these surface signatures, as well as the cause of the presence of open-framework gravel in the subsurface. A suffusion model for sandy gravel was used to describe internal erosion. Internal erosion effectively transforms the sandy gravel into gravel, revealing open-framework gravel zones in the paleo-valley. Contact erosion in gravel can be triggered by suffusion, showing that new models coupling suffusion and contact erosion are needed to model internal erosion in sandy gravels. •Finite element modelling of internal erosion in a sandy-gravel paleo-valley supporting a riveer dike, and subjected to successive floods.•Internal erosion may help to solve the mystery of the presence of open-framework gravel layers in paleo-valleys.•Suffusion can trigger contact erosion, showing that new models of internal erosion coupling suffusion and contact erosion are needed.